A diagnosis of difficulties in answering questions of circle material on junior high school students - Minhajjul Abidin; Heri Retnawati (Graduate School, Universitas Negeri Yogyakarta, 2019)
This research is aimed at describing (1) the characteristics of items about a diagnostic test of circle material in mathematics, (2) how significant the percentage of students' types of errors in answering the questions, and (3) the diagnosis of students' difficulties in answering the questions based on DINA model. This research is quantitative descriptive research involving eighth graders of junior high school in East Lombok regency as the population. The sample was chosen by a proportionate random sampling technique, consisting of 105 students for preliminary field testing and 416 students for main field testing. The instrument of this study was a diagnostic test using a four-option multiple-choice format. Data on students' responses were analyzed using the R program with CDM (Cognitive Diagnostic Model) DINA model, which requires underlying attributes for each item. The results show that: (1) the diagnostic test instrument had met the qualitative and quantitative content validity; (2) the percentage of students' answers retrieved from the conceptual error is 18.47%, 9.99% is interpretation error, the procedural error is 7.80%, and counting error is 14.57%; (3) based on the results of the analysis with DINA model, students' error in answering the questions of the circle material in mathematics are dominantly caused by students' lack of mastery on solving problems associated to the circumference of a circle, that is, (A28) the ability to calculate the length of a path, and (A29) the ability to calculate many rounds on wheels.